ARAH EVALUASI PAJAK TRANSFER KENDARAAN BERMOTOR DI DINAS PENDAPATAN DAERAH KOTA PALEMBANG - Apriani Br Barus; Ermadiani Ermadiani; Eka Meirawati (AKUNTABILITAS, 2013)
The transfer tax of motor vehicle is one of the local taxes that give a bigger significantly to the original revenue receipts. With the more development the making of motor vehicle technologi and people taste are always changing cause the transfer ownersip of a motor vehicle between one party and another party is very fast grow up. This research be made to evaluate the implementationof the adoption and acceptance the transfer tax of motor vehicle and efforts to see was has been made in inproved accept of the transfer tax of motor vehicle.Collect the transfer tax of motor vehicle based in South Sumatera provincia regulation number 3 year of 2011 about regional taxes. Its implementing regulation based on Southern Sumatera governor regulation number 11 ini years 2012. Implementation of collected already running with the legistation in force even though there are some technical obstacles in the implementation of the collection.This study uses descriptive qualitative analysis. The analysis is done qualitatively based on the data and information obtained during the study were associated with theories and concepts with collect the transfer tax of new motor vehicle administration.